Empirical Analysis of Entrepreneurship and Economic Growth - Stel, André van (International Studies in Entrepreneurship, 2006)
The importance of entrepreneurship for achieving economic growth in contemporary economies is widely recognized, both by policy makers and economists. However, empirical evidence linking entrepreneurship to economic growth is scarce. Empirical Analysis of Entrepreneurship and Economic Growth investigates the relation between entrepreneurship and economic growth at the country and regional level. The work contributes to our understanding of how entrepreneurship may affect economic growth. Among others, it is investigated whether the impact of entrepreneurship on economic growth varies with the development level of an economy, with the sector of economic activity, and with the quantity and quality of entrepreneurial supply. Empirical evidence is provided showing that the impact is dependent upon all these three aspects.